Crystal structure of (E)-2-(4-hydroxy-3-methoxybenzylidene)-6-methoxy-3,4-dihydronaphthalen-1(2H)-one, C19H18O4 - El-Sayed, Nahed Nasser Eid; Almaneai, Norah M.; Ghabbour, Hazem A.; Alafeefy, Ahmed Mahmoud (Walter de Gruyter GmbH, 2016)
C19H18O4, orthorhombic, Pbcn, a=21.1472(8) Å, b= 9.7978(4) Å, c=14.5181(6) Å, V =3008.1(2) Å3, Z =8, Rgt(F)=0.0520, wRref(F2)=0.1194, T =100(2).